Associations between interpregnancy interval and preterm birth by previous preterm birth status in four high‐income countries: a cohort study. (14th December 2020) - Marinovich, ML; Regan, AK; Gissler, M; Magnus, MC; Håberg, SE; Mayo, JA; Shaw, GM; Bell, J; Nassar, N; Ball, S; Gebremedhin, AT; Marston, C; et al.
Abstract : Objective: To investigate the effect of interpregnancy interval (IPI) on preterm birth (PTB) according to whether the previous birth was preterm or term. Design: Cohort study. Setting: USA (California), Australia, Finland, Norway (1980–2017). Population: Women who gave birth to first and second ( n = 3 213 855) singleton livebirths. Methods: Odds ratios (ORs) for PTB according to IPIs were modelled using logistic regression with prognostic score stratification for potential confounders. Within‐site ORs were pooled by random effects meta‐analysis. Outcome measure: PTB (gestational age <37 weeks). Results: Absolute risk of PTB for each IPI was 3–6% after a previous term birth and 17–22% after previous PTB. ORs for PTB differed between previous term and preterm births in all countries ( P‐for‐interaction ≤ 0.001). For women with a previous term birth, pooled ORs were increased for IPI <6 months (OR 1.50, 95% CI 1.43–1.58); 6–11 months (OR 1.10, 95% CI 1.04–1.16); 24–59 months (OR 1.16, 95% CI 1.13–1.18); and ≥ 60 months (OR 1.72, 95%CI 1.60–1.86), compared with 18–23 months. For previous PTB, ORs were increased for <6 months (OR 1.30, 95% CI 1.18–1.42) and ≥60 months (OR 1.29, 95% CI 1.17–1.42), but were less than ORs among women with a previous term birth ( P < 0.05). Conclusions: Associations between IPI and PTB are modified by whether or not the previous pregnancy was preterm. ORs for short and long IPIs were higher among women with a previous term birth than a previous PTB, which for short IPI is consistent with the maternal depletion hypothesis. Given the high risk of recurrence and assuming a causal association between IPI and PTB, IPI remains a potentially modifiable risk factor for women with previous PTB. Tweetable abstract: Short versus long interpregnancy intervals associated with higher ORs for preterm birth (PTB) after a previous PTB. Tweetable abstract: Short versus long interpregnancy intervals associated with higher ORs for preterm birth (PTB) after a previous PTB.